Sistem Informasi Manajemen pada Apotek Christ Berbasis Website - Ignatius Christian; Lily Puspa Dewi; Justinus Andjarwirawan (Jurnal Infra, 2017)
Christ Pharmacy located in Surabaya is a business that engages in pharmacy, as a medicine providers. Business process are ordering and purchase medicines to the supplier, sells drugs to patient and service BPJS program from government. Business process performed is still based on human activities, so some times there is risk of human error that can cause problems. In addition, the reporting process is still work manually.Seeing the problems, it will require a solution that information management system based on website for pharmacy to be computerized and improve the control of business process at the pharmacy. Management information system that is built using PHP, HTML, jQuery and MySQL for database management. The resulting from system are recording data master, supplier, drug categories, conversion. Furthermore, recording sales and purchasing process that include ordering unit, purchase return and drug sales and service BPJS. The report generated from this program are income statement, BPJS statement, and another reports.Overall, this program has been suitable with the needs of the pharmacy. The results of questionnaire that was distributed to pharmacies known that 96% of users found the design of the program is considered good, 68% of the facilities for obtaining information considered good, 72% of users found good about the completeness and clarity of the information is considered good. Rate programs overall 80% by the user.